Neoadjuvant chemotherapy improves survival of patients with upper tract urothelial carcinoma. Issue 12 (13th March 2014) - Porten, Sima; Siefker‐Radtke, Arlene O.; Xiao, Lianchun; Margulis, Vitaly; Kamat, Ashish M.; Wood, Christopher G.; Jonasch, Eric; Dinney, Colin P. N.; Matin, Surena F.
Abstract : BACKGROUND: High‐grade upper tract urothelial carcinoma (UTUC) is frequently upstaged after surgery and is associated with uniformly poor survival. Neoadjuvant chemotherapy may offer a way to improve clinical outcomes. The authors compared the survival rates of patients with UTUC who received neoadjuvant chemotherapy before surgery with the rates among patients who did not. METHODS: A retrospective review was conducted of patients with high‐risk UTUC who received neoadjuvant chemotherapy followed by surgery from 2004 to 2008 (study group) compared with a matched cohort who underwent initial surgery from 1993 to 2003 (control group). Fisher exact tests, Wilcoxon rank‐sum tests, and Kaplan‐Meier methods were used. The log‐rank test and Cox proportional‐hazards models were used to evaluate the association of the 2 outcomes with patient, treatment, and tumor characteristics in univariate and multivariate models. RESULTS: Of 112 patients, there were 31 in the study group and 81 in the control group. Patients who received neoadjuvant chemotherapy had improved overall survival (OS) and disease‐specific survival (DSS) with a 5‐year DSS rate of 90.1% and a 5‐year OS rate of 80.2% versus DSS and OS rates of 57.6% for those who underwent initial surgery ( P  = .0204 and P  = .0015, respectively). In multivariate analyses, the neoadjuvant group had a lower risk of mortality (OS: hazard ratio, 0.42 [ P  = .035]; DSS: hazard ratio, 0.19 [ P  = .006]). CONCLUSIONS: Neoadjuvant chemotherapy improved the survival of patients with UTUC compared with a matched historic cohort of patients who underwent initial surgery. Patients with high‐risk UTUC should be considered for neoadjuvant chemotherapy in view of the limited opportunity to administer effective cisplatin‐based chemotherapy after nephroureterectomy. Cancer 2014;120:1794–1799 . © 2014 American Cancer Society . Abstract : Neoadjuvant chemotherapy improves survival in patients with high‐risk upper tract urothelial carcinoma compared with a matched historic cohort of patients treated with initial surgery.